Helminth parasites prevalence and distribution among Sheep in Gudaya Bila District, East Wallaga, Ethiopia - Tesema, Gemeda; Tesfaye, Solomon; Bekele, Damtew (Journal of Parasite Research, 2023)
Helminth parasite infections in sheep are of major veterinary importance in many agro-ecological zones and are a primary factor in the productivity of sheep. The main objective of this study was to determine helminth parasites prevalence and their economic loss caused on sheep with its control approach at the study area. A cross-sectional study using a simple random sampling procedure was used to study helminth parasite identification at Gudaya Bila district during 2022 in two seasons of the year: winter (January - March) and summer (June - August). Out of 384 sheep chosen at random sampling from five Kebeles in the Gudaya Bila district (Welenelemu, Harogodisa, Chalejima, Hagelogidami, and Bila) that underwent flotation and sedimentation procedures, about 149 were infected by ay helminth parasites, with an overall prevalence 38.8%. Regarding the distribution of helimenth parasites at the class level, the prevalence was 13.9%, 11.7%, and 3.9% in trematoda, nematode, and cestoda, respectively. The helminth species that had highest prevalence were Fasciola species (19.5%), Haemonchus species (14.76%), Strongyloides species (10.74%), and Schistosoma species (9.4%), and those that had the least prevalence were Moniezia species (6.04%), Paramphistomum species (5.4%), Taenia species (4.02%), Nematodirus species (3.3%) and Trichostrongylus species (1.34 %). The summer season was favorable for helminths parasite transmission. The prevalence of helminths in the summer season was 98 (25.5%), and in the winter season it was 51 (13.3%). The study shows that the gastrointestinal helminth parasite was a major health problem and had an impact on the production of sheep in the study area. Therefore, a detailed study should be conducted to identify the parasite at the species level, and further investigation will be needed to study the association of the prevalence of helminth parasites within age, sex and the agroecology of sheep in the area. Then educating the people about the impacts of helminths is needed to control them.
Keywords: Economic loss; Helminths Parasites; Medicinal plant; Sheep; Traditional control.